Establishing a cryopreservation protocol for patient‐derived xenografts of prostate cancer. Issue 11 (18th June 2019) - Porter, Laura H.; Lawrence, Mitchell G.; Wang, Hong; Clark, Ashlee K; Bakshi, Andrew; Obinata, Daisuke; Goode, David; Papargiris, Melissa; MURAL; Clouston, David; Ryan, Andrew; Norden, Sam; et al.
Abstract: Background: Serially transplantable patient‐derived xenografts (PDXs) are invaluable preclinical models for studying tumor biology and evaluating therapeutic agents. As these models are challenging to establish from prostate cancer specimens, the ability to preserve them through cryopreservation has several advantages for ongoing research. Despite this, there is still uncertainty about the ability to cryopreserve PDXs of prostate cancer. This study compared three different cryopreservation protocols to identify a method that can be used to reproducibly cryopreserve a diverse cohort of prostate cancer PDX models. Methods: One serially transplantable prostate cancer PDX from the Melbourne Urological Research Alliance cohort was used to compare three cryopreservation protocols: slow freezing in fetal calf serum (FCS) with 10% dimethyl sulfoxide (DMSO), FCS with 10% DMSO supplemented with the Rho‐associated kinase (ROCK) inhibitor Y‐27632 and vitrification. The efficiency of the slow freezing protocols was then assessed in 17 additional prostate cancer PDXs. Following cryopreservation, PDXs were re‐established in host mice that were either intact and supplemented with testosterone or castrated. Graft take rate, tumor growth, histological features, and transcriptome profiles before and after cryopreservation were compared. Results: Slow freezing maintained the viability and histological features of prostate cancer PDXs, and the addition of a ROCK inhibitor increased their growth following cryopreservation. Using the slow freezing method, we re‐established 100% of PDXs grown in either testosterone‐supplemented or castrated host mice. Importantly, the long‐term tumor growth rate and transcriptome profile were maintained following cryopreservation. Conclusion: This study has identified a protocol to reliably cryopreserve and re‐establish a diverse cohort of serially transplantable PDXs of prostate cancer. This study has the potential to significantly improve the practicality of maintaining PDX models. Cryopreservation may also increase the accessibility of these important resources and provide new opportunities for preclinical studies on a broader spectrum of prostate tumors.